Repartition Des Glossines Dans La Province De L’ogooue Ivindo Ancien Foyer De Trypanosomose Humaine Africaine - Roland, Zinga Koumba Christophe; Ornella, Mbang Nguema; Donald, Midoko Iponga; Franck, Mounioko; Shango, Mutambwe; François, Mavoungou Jacques; Bertrand, M’batchi (European Scientific Journal, ESJ, 2016)
In Gabon, the situation of Human African Trypanosomosis (HAT) remains unclear. In addition, several historical foci existing in many provinces have not been explored for over 15 years. Yet many studies have shown that this country has to offer favorable ecosystems for the development of tsetse major vectors of HAT. To verify a risk of transmission of sleeping sickness, a tsetse inventory was conducted in the province of Ogooué Ivindo historic home of HAT. Vavoua and Nzi traps were placed in four characteristic habitats of the province: National Park Ivindo, Zadié Village, Forest of Zadié and baï (clearing) of Momba. A total of 2383 flies were captured: 1680 flies in the clearing of Momba, 437 flies in the primary forest Zadié, 139 in the National Park Ivindo and 12 in Zadié village. Moreover, these flies were divided into 7 species Glossina frezili, Glossina fusca congolensis, Glossina nashi, Glossina palpalis palpalis, Glossina tabaniformis, Glossina fuscipes fuscipes and Glossina tachinoides. Glossina palpalis palpalis (46%) was the most abundant species followed by Glossina fusca congolensis (21%) and Glossina nashi (16%). Glossina fuscipes fuscipes (6%), Glossina frezili (4%), Glossina tabaniformis (4%) and Glossina tachinoides (3%) were the least caught species. These results have shown that the province of Ogooué Ivindo still remains infested by tsetse flies. Also, further study monitoring these insects is essential to clarify the epidemiological importance of these vectors on human health in this province.